Special Economic Zones : An Operational Review of Their Impacts - World Bank Group (World Bank, Washington, DC, 2017)
Policy-makers across developing economies are implementing different forms of special economic zones (SEZs): programs intended to catalyze economic growth. The SEZ program is aimed at attracting foreign direct investment (FDI) to increase firm-level investment and improve firm-level productivity by enhancing firm-level coordination, networks, and innovation. The purpose of this operational review is to inform and to identify and document lessons from the application of these policies across countries and across the World Bank’s project portfolio. The report reviews the SEZ programs, and the characteristics and contexts that are associated with the success of SEZ policies. The report also adds to the general SEZ debate of whether the benefits generated by SEZs are restricted to the firms within the walls of the SEZs with limited social benefit; or whether SEZs eventually lead to spillovers that support structural change generating high social benefits. The report is structure as follows: chapter one gives introduction. Chapter two, provides a brief literature review of SEZ theory and performance. Chapter three provides an overview of the dataset developed for this work. Chapter four presents the econometric estimation using the dataset (for the explanatory variables) and nighttime lights data over 5 years as a measure of success (and dependent variable). Finally, chapter five focuses on the World-Bank-Group-funded projects that contain an SEZ component and assess the factors determining success and failures of SEZs.